EVALUATION OF THE DAMAGE TO HUMAN LIFE AND HEALTH IN AZERBAIJAN IN THE SECOND KARABAKH WAR - Farhad G. Mikayilov, Elman ?bishov (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The main purpose of the article is to summarize the methodological basis of compensation to be paid to those killed, injured and disabled as a result of human rights violations and to evaluate the damage done to human life and health in Azerbaijan during the Second Karabakh War. To achieve this goal, the theoretical and methodological foundations were generalized, the experiences of similar countries were taken into account, and evaluations were made on the basis of relevant statistics. Losses were assessed as the sum of the potential income that these countries will receive from the amount of compensation and lump-sum payments to those who died, injured or disabled in countries where compensation will be paid due to the increase in budget expenditures directly based on state aid. It should be noted that current income is estimated on the basis of the country’s average monthly salary and part of the range before retirement age and the duration of the benefit payable based on the legal age limit or the expected life expectancy of the beneficiaries. Evaluated analysis, analysis, synthesis and evaluation methods were used in the conduct of the research. As a result, the amount of damage done to the economy and citizens of Azerbaijan was calculated for the damage done to human life and health with appropriate justifications.